Translation planes of dimension two and characteristic two - N. L. Johnson; T. G. Ostrom (International Journal of Mathematics and Mathematical Sciences)
This article discusses translation planes of dimension two and characteristic two. Let G be a subgroup of the linear translation complement of such a plane π. The nature of G and its possible action on π are investigated. This continues previous work of the authors. It is shown that no new groups occur.